Association between Vitamin D and serum ferritin levels in anemic women of child bearing age in Malakand KPK - Fatima Saadat, Umar Sabir, Shahid Waseem, Hina Hakim, Naveed Ahmad, Zia Ul Arifeen, Nowsherwan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Vitamin D deficiency is a widespread issue around the world. Ferritin is a massive protein with 24 subunits and light and heavy chains. The body's intracellular iron storage is represented by ferritin. Vitamin D deficiency and iron deficiency are frequently found together. Mechanistic interactions between iron and vitamin D metabolism are now thought to be at the root of these correlations. Objective: 1. To determine mean vitamin D and serum Ferritin in anaemic women of child bearing aged between 15-49 years. 2. Correlation between vitamin D level and serum Ferritin in anemic women of child bearing age. Methodology: A Cross sectional survey was conducted from October 2020 to April 2020 at Malakand. A total of 196 females of child bearing age 15-49 years who were not currently taking any vitamin D supplementation were selected through consecutive sampling. The study participants were interviewed by using a preformed questionnaire. For determining haemoglobin, Ferritin and vitamin D levels, blood samples were taken from all participants in aseptic environment. The data were analyzed by statistical method generated on the computer software SPSS 23. Result: Study results revealed that there is no significant association between anaemia and vitamin D level but there is a significant association between anaemia and serum ferritin showing p value p<0.05. Furthermore Mean age of the study participants was 30.2806±9.176, mean weight, Height, Hemoglobin, Vitamin D and serum Ferritin was 62.1684±10.16062, 159.7398±32.84960, 9.5592±1.12275, 25.701±13.8711 and 12.1738±12.32928 respectively. Conclusion: It was concluded that there is not a significant association between anaemia and vitamin D level but there is a significant association between anaemia and serum ferritin showing p value p=0.017 Moreover no association between vitamin D and serum ferritin level among anaemic females of child bearing age were seen .